Adapted text benefits for teachers and students: A retroactive case study - Tucker, Lauren (Journal of Learning and Teaching in Digital Age, 2021)
This case study retrospectively reflects on a self-contained teacher’s decision to pair publisher-created adapted text with audio support as part of a multicomponent reading intervention. She evolved from creating her own adapted text to implementing publisher-created adapted text throughout a school year. The study analyzed students’ reading comprehension test scores throughout the year to examine the influence of publisher-created adapted text embedded within a multi-component reading intervention. The Related-Samples Wilcoxon Signed Rank Test revealed significance (p=.043) between students’ fall and spring Reading Inventory scores, with a moderate effect size (r=.562). The teacher made the instructional decision to implement publisher-created adapted text which eliminated time consuming self-adaptation of materials (Browder et al., 2007) and her students continued to make progress with this shift of materials with some demonstrating significant progress by the end of the school year.
Keywords: dept.sed

Universally Designing in Universal Chaos. - Tucker, Lauren (Remote Teaching and Learning: Reflections and Practical Advice, 2021)
Looking back on a year of tumultuous teaching and learning amid restrictions set in place after the COVID-19 pandemic began in early 2020, Remote Teaching and Learning: Reflections and Practical Advice focuses not only on the trials and tribulations higher ed faculty have endured but also the insights learned, silver linings revealed, and successes achieved through emergency remote teaching. Hear from 20 educators whose contributions include: reflections on pandemic teaching; strategies and practical advice; and resources for students.Whether you’re returning to a face-to-face classroom, continuing to teach online, or exploring hybrid or HyFlex teaching, you’ll find wisdom, advice, and observations from educators with a shared commitment to student learning. Includes student handouts to use in your classroom!
Keywords: dept.sed

What are we optimizing for in autism screening? Examination of algorithmic changes in the M-CHAT - Schjølberg, Synnve; Shic, Frederick; Volkmar, Fred R.; Nordahl-Hansen, Anders; Stenberg, Nina; Torske, Tonje; Larsen, Kenneth; Riley, Katherine; Sukhodolsky, Denis G.; Leckman, James F.; Chawarska, Katarzyna; Øien, Roald A. (Autism research : official journal of the International Society for Autism Research, 2021)
The present study objectives were to examine the performance of the new M-CHAT-R algorithm to the original M-CHAT algorithm. The main purpose was to examine if the algorithmic changes increase identification of children later diagnosed with ASD, and to examine if there is a trade-off when changing algorithms. We included 54,463 screened cases from the Norwegian Mother and Child Cohort Study. Children were screened using the 23 items of the M-CHAT at 18 months. Further, the performance of the M-CHAT-R algorithm was compared to the M-CHAT algorithm on the 23-items. In total, 337 individuals were later diagnosed with ASD. Using M-CHAT-R algorithm decreased the number of correctly identified ASD children by 12 compared to M-CHAT, with no children with ASD screening negative on the M-CHAT criteria subsequently screening positive utilizing the M-CHAT-R algorithm. A nonparametric McNemar's test determined a statistically significant difference in identifying ASD utilizing the M-CHAT-R algorithm. The present study examined the application of 20-item MCHAT-R scoring criterion to the 23-item MCHAT. We found that this resulted in decreased sensitivity and increased specificity for identifying children with ASD, which is a trade-off that needs further investigation in terms of cost-effectiveness. However, further research is needed to optimize screening for ASD in the early developmental period to increase identification of false negatives. © 2021 The Authors. Autism Research published by International Society for Autism Research and Wiley Periodicals LLC.
Keywords: Article; Autism Spectrum Disorder; Autistic Disorder; Checklist; Child; Cohort Studies; Female; Humans; Infant; M CHAT R algorithm; M CHAT algorithm; Mass Screening; McNemar test; Mothers; algorithm; autism; checklist; child; cohort analysis; controlled study; cost effectiveness analysis; dept.sed; developmental stage; diagnostic accuracy; diagnostic test accuracy study; early diagnosis; false negative result; female; gold standard; human; infant; major clinical study; mass screening; mother; nonparametric test; peer-reviewed; procedures; process optimization; psychometry; reference value; scoring system; sensitivity and specificity; statistical significance

Partnering to create a core communication board to improve theater experiences - Tucker, Lauren (Assistive Technology Outcomes and Benefits, 2021)
This article outlines a partnership between a nonprofit theater in Connecticut and pre-service special education teachers at a local university. The goal of the collaboration was to increase the accessibility of the sensory-friendly performances and events designed for students in PK-12. The process of creating visual supports and a core communication board is shared, in addition to the designing of training and implementation phases. The project not only resulted in improved supports for the school-aged sensory-friendly events for the next season, but also in a demonstrable perspective shift on the importance of inclusivity and community communication supports among pre-service teachers and community members. © 2021, Assistive Technology Industry Association. All rights reserved.
Keywords: dept.sed; peer-reviewed; ⛔ No DOI found

Initial support for a behavioral skills training package with computer-based instruction to teach conversation skills to adults with autism spectrum disorders, with an assessment of socially meaningful behavior change1 - Groskreutz, Nicole C.; Groskreutz, Mark P. (Evidence-Based Communication Assessment and Intervention, 2021)
Keywords: Article; Asperger syndrome; adolescent; adult; autism; behavior change; behavior therapy; clinical article; communication skill; computer aided design; conversation; dept.sed; follow up; human; parental attitude; patient attitude; peer-reviewed; skill; social validity

Transfer of writing skills across genres among deaf and hard of hearing elementary writers - Dostal, Hannah M.; Wolbers, Kimberly A.; Weir, Joan (International Journal of Educational Research, 2021)
Thirty-seven deaf and hard of hearing (DHH) students in grades four through six participated in a year of Strategic and Interactive Writing Instruction, an approach to writing instruction designed to be responsive to DHH students’ unique language experiences and profiles. The current study investigated the transfer of writing skills between genres by analyzing participants’ recount, information report, and persuasive writing samples at four time points: at the beginning of the academic year, immediately before genre-focused instruction, at the end of 9 weeks of instruction in a genre, and 9 weeks after the conclusion of instruction in a genre. Results from the study demonstrate that DHH students transfer genre-specific writing skills between genres. © 2021 The Authors
Keywords: dept.sed; peer-reviewed

Preparing educators for inclusive bilingual education: A boundary crossing laboratory between professional groups - Martínez-Álvarez, P; López-Velásquez, A; Kajamaa, A (Cultural-Historical Psychology, 2021)
Teacher education programs prepare candidates for bilingual, English as a second language, or special education as separate professionals. This creates challenges when teaching bilingual children with disabilities. There is a need to cross boundaries combining expertise and preparing teachers for children's uniqueness. Responding to this need, the researchers organized a change laboratory with 14 professors and two State Department of Education consultants. The study explored boundary expressions and their relationship to the larger activity. It also looked at the learning that took place during boundary crossing efforts. Boundaries were identified around bilingual teacher preparation, cross-disciplinary programmatic, and paradigmatic aspects. While boundary crossing at the intrapersonal level and at the interpersonal level were important, the need to engage multiple institutions was centered. In addition, the discussion manifested that for inclusive bilingual education teacher preparation, there was a need to go beyond the institutional level to reach to policy makers and address the sociopolitical resistance against bilingual education. Throughout the study, participants engaged primarily in the epistemic learning actions of analyzing and modeling. Through volitional actions, the participants realized a renewed object for their activity. This study widens the understanding of possibilities for taking shared educational responsibility through boundary crossing between professionals in preparation programs. © 2021. All Rights Reserved.
Keywords: dept.sed; peer-reviewed

The Diagnosis of Autism: From Kanner to DSM-III to DSM-5 and Beyond - Rosen, Nicole E.; Lord, Catherine; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2021)
In this paper we review the impact of DSM-III and its successors on the field of autism—both in terms of clinical work and research. We summarize the events leading up to the inclusion of autism as a “new” official diagnostic category in DSM-III, the subsequent revisions of the DSM, and the impact of the official recognition of autism on research. We discuss the uses of categorical vs. dimensional approaches and the continuing tensions around broad vs. narrow views of autism. We also note some areas of current controversy and directions for the future.
Keywords: Article; Asperger syndrome; Autism; Autism Spectrum Disorder; Autistic Disorder; Categorical; DSM; DSM-5; DSM-III; DSM-IV; Diagnostic and Statistical Manual of Mental Disorders; Dimensional; History; Humans; ICD-10; ICD-11; Psychology; Recognition; autism; clinical feature; clinical research; cognition; cultural factor; dept.sed; dept.swk; developing country; echolalia; ethnic group; human; language ability; medical history; peer-reviewed; pervasive developmental disorder not otherwise specified; psychiatric diagnosis; psychological aspect; race; sex difference; social class; symptom; tension

Literacy development at camp: Leveraging language models - Dostal, Hannah M.; Scott, Jessica A.; Weir, Joan; Kang, Ki Y.; Amadi-Ihebuzor, Chidinma; Bernard, Teri-Ann (Reading Teacher, 2021)
There is little research on effective educational experiences for deaf and hard-of-hearing (d/hh) children in Jamaica. Using a formative and design experiment framework, in this project we explored the potential efficacy of an intensive literacy camp that provided professional development for d/hh adults working in classrooms with d/hh children, and provided literacy instruction for elementary-age campers. We found that the children improved in all tested areas, and observations of d/hh adults provided evidence that with minimal training they were able to implement important facets of literacy instruction with the campers. Further research on these types of experiences and their potential for lasting impact after the camp is necessary. © 2021 International Literacy Association
Keywords: dept.sed; peer-reviewed

Student perception on the impact of the Livescribe smartpen as an accommodation - Tucker, Lauren; Zamfir, Bogdan (Universal Access in the Information Society, 2021)
The goal of this exploratory qualitative study was to determine how students with disabilities in higher education are using the Livescribe smartpen in their note-taking process and the perceived impact on their academic tasks. Based on participant interviews, many are using the Livescribe smartpen for recording class lectures while taking notes and for engaging with the content outside of the class session. All but one participant reported a perceived positive impact from the use of the Livescribe pen. The positive impacts included improved focus, higher academic outcomes, independence, and capturing complete notes. One unexpected trend that was revealed is that the majority of the participants adjusted their use of the Livescribe smartpen accommodation based on the professor’s teaching style and course structure. © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.
Keywords: Course structure; Higher education; Information science; Information systems; Note taking; Qualitative study; Software engineering; Student perceptions; Teaching styles; dept.sed; peer-reviewed

Seeing the forest and the trees: Disentangling autism phenotypes in the age of DSM-5 - Volkmar, Fred R.; Woodbury-Smith, Marc; Øien, Roald A. (Development and Psychopathology, 2021)
This paper, written in honor of Professor Ed Zigler, focuses on some of the themes in developmental disabilities research that were so central to his work. It has now been nearly 80 years since Leo Kanner first identified the prototypic form – early infantile autism – of what is now autism spectrum disorder. In this article we summarize the development of the concept and the important accumulation of knowledge over time that has now led us to the recognition of a broader autism phenotype just as, at the same time, the current official diagnostic system in the USA has narrowed the concept. We also address current controversies regarding autism as the diagnosis is impacted by age and developmental factors, gender, and cultural issues. In parallel to the work on intellectual deficiency and development pioneered by Zigler and his colleagues, we summarize some of the challenges for the years ahead.
Keywords: Autism Spectrum Disorder; Autistic Disorder; Diagnostic and Statistical Manual of Mental Disorders; Humans; Phenotype; Psychology; Recognition; autism; dept.sed; human; peer-reviewed; phenotype

Motivating students with learning disabilities to read - Wei, Yan; Spear-Swerling, Louise; Mercurio, Mia (Intervention in School and Clinic, 2021)
Students may lack the motivation to read for many reasons, including inadequate access to interesting texts, limited encouragement to read for pleasure from adults, instructional practices that do not foster engagement in learning, or a history of reading failure. This article focuses on students with reading disabilities who may have a long-standing dislike of reading born of repeated negative experiences with learning to read. Motivating these students to read for pleasure may seem like an unattainable goal. However, past difficulties in reading do not necessarily mean that children will dislike reading forever. In conjunction with appropriate academic interventions, student interest in reading might be improved by motivational interventions aligned with a theoretical framework discussed in this article: (a) choosing interesting texts to read, (b) stimulating knowledge-based interest, and (c) enhancing task-based interest.
Keywords: dept.sed; peer-reviewed

School Leadership for Learning: Learning Theory to Improve Professional Practice - Gregory, Jess L.; Ben-Avie, Michael; Billups, Felice; Grassetti, Mary; Hesser, Tiffany; Lawlor, Jennifer Lynne; Martone, Drey; Maykel, Cheryl; Minkos, Marlena L.; Paslov, Linda; Trombly, Christopher; Tucker, Lauren; et al. (Jess L. Gregory, 2021)
Keywords: Educational leadership; School administrators; Handbooks, manuals, etc; In-service training; School administrators; In-service training; Teachers; dept.edl; dept.sed; faculty_collection